Occupational stress among health care workers : a test of the job demands-control model - Landsbergis, Paul A. [Verfasser] (My University, 1988)
"Models of occupational stress have often failed to make explicit the variable of control over the environment, as well as the role of job socialization in shaping personality characteristics and coping behaviour. This neglect has helped maintain the focus of stress reduction interventions on the individual. A new model of occupational stress developed by Robert Karasek incorporates control and socialization effects and has successfully predicted the development of heart disease and pschychological strain. A survey instrument derived from the model was distributed to 771 hospital and nursing home employees in New Jersey, and 289 (37,5 per cent) were returned. Respondents did not significantly differ from non- respondents by age, sex, job tenure, union membership status, job satisfaction, job perceptions and attitude towards employer and union. The results support the hypothesis that reported job strain (job dissatisfaction, depression, psychosomatic symptoms) and burnout is significantly higher in job that combine high workload demands with low decision latitude. This association remained significant after controlling for age, sex, education, marital status, children, hours worked per week and shift worked. Other job charakteristics (job insecurity, physical exertion, social support, hazard exposure) were also associated with strain and burnout. The survey instrument also identified high strain jobtiles in the surveyed workplaces. The results are discussed in relation to directions for future research, research on stress in nursing, and approaches to stress reduction." (author's abtract) ((en)) In der Studie wird verschiedenen Determinanten der Arbeitsbelastung nachgegangen. Als empirische Grundlage dient die Befragung von Angestellten der amerikanischen Gesundheitsdienste. Die Ergebnisse der Untersuchung weisen darauf hin, dass die Arbeitsbelastung in Berufen, welche hohe Leistungsanforderungen mit einem geringen Entscheidungsspielraum verbinden, besonders hoch ist. (IAB)
Beruflicher Stress bei Arbeitnehmern im Gesundheitsdienst.
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 2.3.1 Arbeitsteilung & -organisation; T 4.8 Arbeitswissenschaften; Krankenpflegepersonal; Care work; Berufsproblem; Berufliche Sozialisation; Soziale Kontrolle; Arbeitsbelastung; Arbeitsanforderungen; Quantitative Angaben